FORECASTING OF BASIC STRUCTURAL PARAMETERS OF CONCRETE DRUM MIXERS - Nazarenko, I. I.; Klymenko, M. O. (Техніка будівництва, 2020)
The modern models and calculation methods of the basic construction parameters of drum concrete mixers are analyzed and the limits of the probable change of these parameters for the various designs of the mixing drums and their modes of operation are determined. There are comparison of the results obtained in previous studies with the results of other authors, as well as the data obtained from technical sources. The analysis is aimed at establishing predictive reference values of the basic design parameters for newly created gravity drum mixers.